“I Love and Respect the Entire Czech People”. Traces of Eliza Orzeszkowa’s Czechophile Activity Based on Letters to Edvard Jelinek - Błasińska, Aleksandra (Slavistica Vilnensis, 2023)
The article, based on Eliza Orzeszkowa’s letters to Edvard Jelínek from 1881–1896, presents the relationship between the two writers. They were guided by the common idea of vzajemnosti, i.e. promoting cultural activities among the Slavs, aimed at bringing nations together. In this regard, Orzeszkowa undertook many initiatives in cooperation with the Czech writer. The first was an attempt to publish in Polish the work The Fall and Rebirth of the Czech Nation, presenting the history of the Czechs. On the pages of the letters, the project of publishing an anthology works by famous Czech poets and prose writers translated by Czesław Jankowski, Bronisław Teodor Grabowski, Władysław Bełza and Wilhelmina Zyndram-Kościałkowska was discussed. The income from the sale of the publication was planned to be used to rebuild the National Theater in Prague (Národní divadlo), which burned down in 1881. The writer also organized a fundraising for this purpose at the “Orzeszkowa i S-ka” bookstore in Vilnius. The last undertaking was the intention to publish Orzeszkowa’s memories from her stay in Prague – it was to familiarize the reader with Czech culture. Even though some of the discussed plans were already advanced, they were not implemented, mainly due to tsarist decrees. This correspondence is therefore a valuable trace of the Polish–Czech cooperation between writers. The quoted fragments of Orzeszkowa’s letters to Jelínek are in the National Literature Museum in Prague (Památník Národního Písemnictví). They have not been released yet.